A Collated and Critical Study of the Xiang'er Commentary to the Laozi - Chai, David, (Asian Studies E-Books Online, Collection 2024., 2024)
This work is a translation of the Xiang'er commentary to the Daodejing and Jao Tsung-i's (1917-2018) supplemental notes and analysis. Jao Tsung-i offers a historically and hermeneutically rich study of the Xiang'er Commentary , discovered in the Mogao caves at Dunhuang in the final years of the Qing Dynasty, and its author Zhang Daoling. Opening a new and fascinating window into the early reception of the Daodejing , Jao Tsung-i also uncovers the important influence texts such as the Scripture of Great Peace (Taiping jing) had on Celestial Masters Daoism and the construction of the Xiang'er commentary .